Effects of SiC/HfC ratios on the ablation and mechanical properties of 3D Cf/HfC-SiC composites. Issue 6 (June 2017) - Yan, Chunlei; Liu, Rongjun; Zhang, Changrui; Cao, Yingbin; Wang, Yanfei
Abstract: Effects of SiC/HfC ratios on the ablation and mechanical properties of 3D Cf /HfC–SiC composites by precursor impregnation and pyrolysis (PIP) process were investigated systematically. Both strength (flexural and compressive strength) and modulus increase as the SiC/HfC ratio are improved. The compact and stiff HfC-SiC matrix in addition to the carbon fiber and PyC interphase with less reaction damage accounts for the improved mechanical properties of Cf /HfC-SiC with higher SiC/HfC ratios. Meanwhile, both weight loss and erosion depth of Cf /HfC-SiC are improved with the increased SiC/HfC ratios. Therefore, in order to balance the ablation and mechanical properties, an appropriate SiC/HfC ratio should be considered.